2019
DOI: 10.1097/md.0000000000015924
|View full text |Cite
|
Sign up to set email alerts
|

Expression of IL-17 and its gene promoter methylation status are associated with the progression of chronic hepatitis B virus infection

Abstract: To explore interleukin-17 (IL-17) and its epigenetic regulation during the progression of chronic hepatitis B virus (HBV) infection. A total of 162 patients with chronic HBV infection, including 75 with chronic hepatitis B (CHB), 54 with hepatitis B-associated liver cirrhosis and 33 with hepatitis B-associated hepatocellular carcinoma (HBV-HCC), were enrolled in this study. Thirty healthy adults of the same ethnicity were enrolled in the control group. Whole venous blood was obtained from the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
0
11
1
Order By: Relevance
“…Epigenetic factors also influence HBV progression. In the PBMC samples, the methylation of IL‐17A promoter gene was found to be positively related to CHB progression (Tian et al, 2019 ). The genotype analysis of HBV infected patients suggested an active participation of −197G>A and 7488T>C SNP in HBV infection.…”
Section: Role Of Il‐17 In Different Viral Infectionsmentioning
confidence: 99%
“…Epigenetic factors also influence HBV progression. In the PBMC samples, the methylation of IL‐17A promoter gene was found to be positively related to CHB progression (Tian et al, 2019 ). The genotype analysis of HBV infected patients suggested an active participation of −197G>A and 7488T>C SNP in HBV infection.…”
Section: Role Of Il‐17 In Different Viral Infectionsmentioning
confidence: 99%
“…In the past 20 years, studies have confirmed that IL‐17A plays a vital role in infectious and non‐infectious diseases such as chronic hepatitis B virus, autoimmune diseases, cancer and ischaemic stroke 4,12,30 . In addition, CD4 + T‐cell subsets that secrete IL‐17A were named as Th17 cells 31 .…”
Section: The Il‐17 and Il‐17 Receptor Familymentioning
confidence: 99%
“…Studies have found that the number of Th17 cells in the peripheral blood of CHB patients signi cantly increased [50], which suggests that Th17 cells play an immune activation role in chronic HBV infection. Th17 cells abnormally differentiated and secreted in ammatory factors, such as IL-17, which aggravated the in ammation of the body [51]. However, Treg cells are mainly immunosuppressive.…”
Section: Discussionmentioning
confidence: 99%